Second Hankel determinant for the class of Bazilevic functions - D. VAMSHEE , Krishna; RAMREDDY, T. (Studia Universitatis Babeș-Bolyai Mathematica, 2015)
The objective of this paper is to obtain a sharp upper bound to the second Hankel determinant H2(2) for the function f when it belongs to the class of Bazilevic functions, using Toeplitz determinants. The result presented here include two known results as their special cases. Mathematics Subject Classification (2010): 30C45, 30C50.